Environmental Manipulations to Increase Hatching Rate of Catfish Eggs (Pangasius sp.): A Review - Rubi Jalu Waspodo (AGRITROPICA : Journal of Agricultural Sciences, 2022)
Catfish is the primary commodity of freshwater consumption fish that is widely cultivated with a high protein content of 68.6% and a high selling price. In addition, catfish meat is believed to be capable of preventing heart and cardiovascular disease because its unsaturated fats. Catfish skin can be used as a source of collagen in the culinary, cosmetic, and health fields. Catfish spawn all year round because of the abundance of food. The environment can help stimulate the synthesis of reproductive hormones in the reproductive activity of catfish. Environmental manipulations such as temperature, pH and salinity have different effects on the hatchability of catfish (Pangasius sp.) eggs. High temperatures can speed up the hatching time of the eggs but drop the hatching percentage and survival rate because high temperature activates the chorionase enzyme containing pseudokeratin which softens fish egg shells. In contrast to the pH treatment, a pH that is too acidic will deactivate the work of the chorionase enzyme so that the shells of fish eggs are difficult to break, resulting in a low percentage of hatching and survival rate with the longest hatching time. Salinity works by balancing the osmoregulatory pressure in the shell with the environment. A high salinity concentration can damage the egg by breaking into and swelling the eggshell, causing a low survival rate. On the other hand, eggs not treated with salinity were reported to have the lowest hatching percentage due to fungi attacking the eggs causing embryos to die. Salinity does not affect egg hatching time.